Molecular dynamics simulation and experimental investigation of the geometrical morphology development of injection-molded nanopillars on polymethylmethacrylate surface - Zhou, Mingyong; Xiong, Xiang; Drummer, Dietmar; Jiang, Bingyan (Computational Materials Science, 2018)
Injection molding is one of the most promising techniques to fabricate polymeric parts with functional surface nanostructures in large numbers. The replication fidelity of nanostructures directly affects their efficiency. In this study, molecular dynamics (MD) simulation and experimental trial for injection molding nanopillars on polymethylmethacrylate (PMMA) surface were constructed in both injection and packing phases. The filling process was investigated by analyzing the snapshots, densities and gyration radiuses. Influences of packing parameters on geometrical morphology were studied. Results showed that the central area of nanopillars was almost voided during the injection phase and polymer melt could barely flow into nano-cavity. Only the edge area was filled in injection phase and circular structure was observed on the top surface in the experiments. Complete filling was mainly achieved in packing phase. PMMA molecules were stretched along the sidewall and gradually enriched due to the nonbonded interactions. Molecules near the cavity surface were highly oriented along the flow direction. The circular structures were increasingly obscure with a higher packing. PMMA melt was adsorbed on cavity surface because of the lyophilicity of nickel mold insert. Experimental study provided consistent regulation with MD simulation in geometrical morphology development of injection-molded nanopillars on PMMA surface.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Geometrical morphology development; Injection molding; Molecular dynamics simulation; Surface nanopillars